Development Of Learning Experiences in the Context of Islamic Religious Education: Current Approaches and Strategies - Mulyati, Yanti; Safwandy Nugraha, Mulyawan (Zona Education Indonesia, 2024)
This study aims to explain the latest strategies and approaches in the development of Islamic Religious Education learning experiences. This research is qualitative, using descriptive-analysis methods, and literature approaches. The results of this study show that the application of appropriate learning models, strategies, approaches, methods and techniques by teachers in Islamic Religious Education subjects is the main key to achieving learning objectives in the form of character building, behavior, character beliefs, and student learning achievement. This is shown by the results of student learning evaluation through classroom action research in Cycles 1 and 2 to Class V students of SD Negeri Sukamantri, Cileunyi District, Bandung Regency proven to have a positive impact on improving student learning experience